2013
DOI: 10.1039/c3tb21090a
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent nanographene oxide as a platform for efficient carboplatin release

Abstract: Nanographene oxides (NGO) with well-defined sizes were produced from graphite via chemical exfoliation and separated into three different size distributions (300 nm, 200 nm, and 100 nm) using intense sonication and sucrose density gradient centrifugation. Prior to carboplatin (CP) loading, the NGO was functionalized with zero generation polyamidoamide (PAMAM) which renders improved dispersibility and stability of the nanocarrier platform in physiological media. Cell viability tests were conducted on pristine N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The size effect of GO in response to different types of cells was systematically evaluated by Yue et al [ 31 ] and the results showed that the micro-sized GO induced much stronger infl ammation responses compared with the nano-sized GO. Along similar lines, Makharza et al [ 32 ] found that GO samples with average widths of 200 and 300 nm exhibited a cytotoxic effect on mesenchymal stem cells (MSCs) and HeLa cells, whereas the GO samples with an average width of 100 nm showed no signifi cant cytotoxicity. Size is also an important factor affecting the distribution of GO after intravenous administration.…”
Section: Reviewmentioning
confidence: 85%
“…The size effect of GO in response to different types of cells was systematically evaluated by Yue et al [ 31 ] and the results showed that the micro-sized GO induced much stronger infl ammation responses compared with the nano-sized GO. Along similar lines, Makharza et al [ 32 ] found that GO samples with average widths of 200 and 300 nm exhibited a cytotoxic effect on mesenchymal stem cells (MSCs) and HeLa cells, whereas the GO samples with an average width of 100 nm showed no signifi cant cytotoxicity. Size is also an important factor affecting the distribution of GO after intravenous administration.…”
Section: Reviewmentioning
confidence: 85%
“…Before one can take advantage of their desirable properties for dental implants, it is important to verify how GO affects cellular behaviours, especially the direct behaviours of BMSCs. Although several studies have tested the effects of GO‐related materials on MSC behaviours, the results varied . In this study, we focused on the concentrations of pristine GO nanosheets directly applied to BMSCs and the consequent cellular behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…It is easily produced in large quantities and is dispersible in polar solvents including water. The epoxy, carboxyl, and hydroxyl groups of GO provide a platform for further chemical functionalization and tailoring specific properties toward novel applications such as chemical sensing platforms and specialized carriers for biomedical applications . Thermal and/or chemical reduction of GO allows removal of the functional groups and opens possibility to increase substantially its electrical conductivity .…”
Section: Introductionmentioning
confidence: 99%